2018
DOI: 10.1139/cjp-2017-0614
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of synthesized Ag and Ag@SiO2 core–shell nanoparticles: a comparative study

Abstract: Spherical bare silver nanoparticles (AgNPs) and silica coated silver nanoparticles (Ag@SiO 2 ) have been prepared by one step chemical reduction method. The optical, structural and morphological studies were done by UV-Vis absorption spectroscopy, X-ray Diffraction (XRD) andTransmission Electron Microscopy (TEM). The antibacterial effects of AgNP and Ag@SiO 2 were further compared based on diameter of zone of inhibition and minimum inhibitory concentration (MIC) test against B. subtilis AST5-2, S. aureus ATCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…However, most of the present therapeutic methods mainly focus on the bactericidal effect, so it is urgent to develop a comprehensive treatment for both anti-bacterial and anti-inflammatory effects. Compared with previously reported Ag-based antibacterial core-shell NPs, bromfenac sodium were loaded into novel hollow core-shell nanoparticles could be given the anti-inflammatory ability of NPs 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the present therapeutic methods mainly focus on the bactericidal effect, so it is urgent to develop a comprehensive treatment for both anti-bacterial and anti-inflammatory effects. Compared with previously reported Ag-based antibacterial core-shell NPs, bromfenac sodium were loaded into novel hollow core-shell nanoparticles could be given the anti-inflammatory ability of NPs 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Acharya et al [ 90 ] demonstrated that Ag@SiO 2 core-shell nanoparticles (~17 nm) had a more substantial antibacterial effect on B. subtilis , S. aureus , Serratia marcescens, and K. pneumoniae than singular Ag NPs (~14 nm) due to controlled and sustainable release of Ag(I). Correspondingly, Gankhuyag et al [ 91 ] and Pal et al [ 92 ] recorded an enhanced bactericidal activity of SiO 2 @AgNPs and Ag-NP hybrid silica films against E. coli cells, respectively.…”
Section: Biological Studiesmentioning
confidence: 99%
“…Various approaches can be used for filter production, with a common method involving the creation of silver/silica nanoparticle systems for coating air filters. Air filter media coated with AgNPs or AgNPs-coated SiO 2 spheres have shown a strong antiviral effect against bacteriophage MS2, without altering the filtration performances. , Haeng et al used AgNPs-coated nanosilica particles to coat air filters, providing effective virucidal action against MS2 viruses. To avoid the use of liquid in the coating process, studies on dry aerosol coatings have been conducted.…”
Section: Introductionmentioning
confidence: 99%